Student protest and the crisis of democracy in India, 1974-1977 - Kent Carrasco, Daniel (CIAN-Revista de Historia de las Universidades, 2024)
In Indian historiography, there is a consensus regarding the important role played by the student movement in precipitating the first great crisis of Indian democracy, associated with the declaration of the state of emergency between 1975 and 1977. However, few efforts have been made to link the trajectories of student politics in that country with other movements that arose in different parts of the world during the 1960s and 1970s. Focusing on the leadership role played by Jayaprakash Narayan in these student protests, this article argues that the student movement of those years in India must be understood as an important episode of the great transformations experienced throughout the Third World in the so-called “global sixties”.
Keywords: global sixties; student movement; Jayaprakash Narayan; third world